Systematic Literature Review: Digital Literacy in the Classroom Teaching - Viona, Elsa; Danim, Sudarwan; Medriati, Rosane; Kristiawan, Muhammad; Susanto, Edy; Oktaria, Sheren Dwi; Macariola, Julie Simon (The Indonesian Institute of Science and Technology Research, 2025)
Digital literacy is not just an additional skill but a basic need that every individual must have in the modern era. This systematic literature review aims to identify the most effective strategies in improving digital literacy in the field of teaching. The stages of this review follow the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-Analyses) reporting standards by searching academic literature through the Scopus database. The included studies meet the criteria that the articles were published between 2024, the studies were written in English, and open access and social sciences were the subject areas. The results of the study found 91 publications related to digital literacy in teaching. The research trend shows a significant increase from year to year. This indicates the increasing attention and urgency of this topic among researchers. A total of 42 countries were identified as the origin of publications, with Indonesia as the country of origin of the most publications. In addition, the main themes were not to be related to potential strategies for digital literacy in teaching, ranging from the use of advanced technology to empowering teachers and students. These strategies aim to create an inclusive, adaptive, and collaborative learning environment where technology becomes a tool to support meaningful learning. By ensuring effective technology integration, adequate teacher training, equity of access, and the use of collaborative teaching methods, digital literacy can become a key foundation for educational success in the digital age.